Respuesta :
Answer:
-(x+6)(x-8)
Step-by-step explanation:
-x²+2x+48
take out the negative
-(x²-2x-48)
factors of 48 with a difference of -2
-8, 6
-(x+6)(x-8)
Answer:
[tex]-(x-8)(x+6)[/tex]
Step-by-step explanation:
The given trinomial is
[tex]-x^2+2x+48[/tex]
By comparing to [tex]ax^2+bx+c[/tex], we [tex]a=-1,b=2,c=48[/tex].
[tex]ac=-1\times 48=-48[/tex]
Two factors of -48 that adds up to 2 are 8,-6.
We split the middle term to obtain;
[tex]-x^2+8x-6x+48[/tex]
We now factor by grouping;
[tex]-x(x-8)-6(x-8)[/tex]
We factor further to obtain;
[tex](x-8)(-x-6)[/tex]
[tex]-(x-8)(x+6)[/tex]